Enhanced glaucomatous damage accompanied by glial response in a new multifactorial mouse model - Reinehr, Sabrina; Girbig, Renée M.; Schulte, Kim K.; Theile, Janine; Asaad, M. Ali; Fuchshofer, Rudolf; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Immunology, 2023)
Introduction Glaucoma is a complex, multifactorial neurodegenerative disease, which can lead to blindness if left untreated. It seems that, among others, immune processes, elevated intraocular pressure (IOP), or a combination of these factors are responsible for glaucomatous damage. Here, we combined two glaucoma models to examine if a combination of risk factors (IOP and immune response) results in a more severe damage of retinal ganglion cells (RGCs) and the optic nerves as well as an additional glia activation. Methods Six-week-old wildtype (WT+ONA) and βB1-Connective Tissue Growth Factor (CTGF) mice (CTGF+ONA) were immunized with 1 mg ONA (optic nerve antigen). A WT and a CTGF control group (CTGF) received sodium chloride instead. IOP was measured before and every two weeks after immunization. After six weeks, electroretinogram (ERG) measurements were performed. Then, retinae and optic nerves were processed for (immuno-) histology. Further, mRNA levels of corresponding genes in optic nerve and retina were analyzed via RT-qPCR. Results Six weeks after immunization, the IOP in CTGF and CTGF+ONA mice was increased. The optic nerve of CTGF+ONA animals displayed the most severe cell inflammation, demyelination, and macroglia activation. Fewer numbers of oligodendrocytes were only observed in WT+ONA optic nerves, while more apoptotic cells triggered by the extrinsic pathway could be revealed in all three glaucoma groups. The number of microglia/macrophages was not altered within the optic nerves of all groups. The loss of neuronal cells, especially RGCs was most pronounced in CTGF+ONA retinae in the central part and this was accompanied by an enhanced activation of microglia/macrophages. Also, Müller cell activation could be noted in CTGF and CTGF+ONA retinae. Discussion In this new model, an additive degeneration could be noted in optic nerves as well as in the number of RGCs. These results suggest a potential additive role of high IOP and immune factors in glaucoma development, which will aid for understanding this multifactorial disease more precisely in the future.